Epidemiology and predictors of survival of MERS-CoV infections in Riyadh region, 2014-2015 - Fahad S. Al-Jasser; Randa M. Nouh; Randa M. Youssef (Elsevier, 2019)
Background: MERS-CoV emerged as a zoonotic disease in Saudi Arabia with 1437 cases as of July 2016. This study aimed at describing the epidemiology of MERS-CoV infection, clinical aspects of the disease and the determinants of survival. Methods: The medical records of Prince Mohamed Bin Abdulaziz Hospital were reviewed between April 2014 and December 2015 to identify admission and discharge with MERS-CoV. Patient's characteristics, epidemiologic and clinical data and laboratory results were extracted and described. Logistic regression analyses were used to model the determinants of the survival of these patients. Significance of the results were judged at the 5% level. Results: 249 confirmed cases were admitted mostly in August (20.48%) and September (14.86%) of the year 2015. A third (39.36%) reported contact with an index case, developed the disease after 6.2 days and continued to shed the virus for 13.17 days on average. The case fatality rate was 20.08%. Independent predictors of being discharged alive among confirmed cases were younger age (ORA = 0.953), breathing ambient air (ORA = 8.981), not being transferred to the ICU (ORA = 24.240) and not receiving renal replacement therapy (ORA = 8.342). These variables explain 63.9% of the variability of patients' status at discharge. Conclusion: MERS-CoV spread from human-to-human as community acquired and nosocomial infection. The study identified high risk patients in need for special medical attention in order to improve patients' outcome. Keywords: MERS-CoV, Epidemiology, Determinants of survival, Saudi Arabia